Dehydropolymerization of H(3)B·NMeH(2) Using a [Rh(DPEphos)](+) Catalyst: The Promoting Effect of NMeH(2) - Adams, Gemma M. (ACS Catal, 2019)
[Image: see text] [Rh(κ(2)-PP-DPEphos){η(2)η(2)-H(2)B(NMe(3))(CH(2))(2)(t)Bu}][BAr(F)(4)] acts as an effective precatalyst for the dehydropolymerization of H(3)B·NMeH(2) to form N-methylpolyaminoborane (H(2)BNMeH)(n). Control of polymer molecular weight is achieved by variation of precatalyst loading (0.1–1 mol %, an inverse relationship) and use of the chain-modifying agent H(2): with M(n) ranging between 5 500 and 34 900 g/mol and Đ between 1.5 and 1.8. H(2) evolution studies (1,2-F(2)C(6)H(4) solvent) reveal an induction period that gets longer with higher precatalyst loading and complex kinetics with a noninteger order in [Rh](TOTAL). Speciation studies at 10 mol % indicate the initial formation of the amino–borane bridged dimer, [Rh(2)(κ(2)-PP-DPEphos)(2)(μ-H)(μ-H(2)BN=HMe)][BAr(F)(4)], followed by the crystallographically characterized amidodiboryl complex [Rh(2)(cis-κ(2)-PP-DPEphos)(2)(σ,μ-(H(2)B)(2)NHMe)][BAr(F)(4)]. Adding ∼2 equiv of NMeH(2) in tetrahydrofuran (THF) solution to the precatalyst removes this induction period, pseudo-first-order kinetics are observed, a half-order relationship to [Rh](TOTAL) is revealed with regard to dehydrogenation, and polymer molecular weights are increased (e.g., M(n) = 40 000 g/mol). Speciation studies suggest that NMeH(2) acts to form the  precatalysts [Rh(κ(2)-DPEphos)(NMeH(2))(2)][BAr(F)(4)] and [Rh(κ(2)-DPEphos)(H)(2)(NMeH(2))(2)][BAr(F)(4)], which were independently synthesized and shown to follow very similar dehydrogenation kinetics, and produce polymers of molecular weight comparable with [Rh(κ(2)-PP-DPEphos){η(2)-H(2)B(NMe(3))(CH(2))(2)(t)Bu}][BAr(F)(4)], which has been doped with amine. This promoting effect of added amine in situ is shown to be general in other cationic Rh-based systems, and possible mechanistic scenarios are discussed.